2020
DOI: 10.1080/14616696.2020.1833066
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and subjective well-being: longitudinal evidence on satisfaction with work and family

Abstract: This paper provides a timely evaluation of whether the main COVID-19 lockdown policiesremote work, short-time work and closure of schools and childcarehave an immediate effect on the German population in terms of changes in satisfaction with work and family life. Relying on individual level panel data collected before and during the lockdown, we examine (1) how family satisfaction and work satisfaction of individuals have changed over the lockdown period, and (2) how lockdown-driven changes in the labour marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
234
7
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(276 citation statements)
references
References 34 publications
(34 reference statements)
17
234
7
18
Order By: Relevance
“…While this seems fine to get a first thorough impression, we should (and authors did) nevertheless treat findings based on such data with some caution. Future research could make use of existing panels and start collecting more representative data, which can also allow for replication and thus support more robust conclusions (Hoenig and Wenz 2020;Möhring et al 2020). In turn, some of the qualitative (small-N) studies were confronted with difficulties in terms of gaining access to particular social groups, particularly while social distancing measures were in place.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this seems fine to get a first thorough impression, we should (and authors did) nevertheless treat findings based on such data with some caution. Future research could make use of existing panels and start collecting more representative data, which can also allow for replication and thus support more robust conclusions (Hoenig and Wenz 2020;Möhring et al 2020). In turn, some of the qualitative (small-N) studies were confronted with difficulties in terms of gaining access to particular social groups, particularly while social distancing measures were in place.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these authors suggest that physically demanding domestic work is compounded by a mental (over)load since women tend to be more concerned about chores and childcare. Reduced well-being for various groups was further reported in Germany: mothersmore so than fathersand childless people, in particular, reported lower levels of satisfaction with family in the aftermath of the pandemic (Möhring et al 2020). Work satisfaction among mothers declined more, compared to fathers, according to another study from Germany (Hipp and Bünning 2020).…”
Section: Social Inequalitiesmentioning
confidence: 98%
“…Studies in Germany reported that during the COVID-19 lockdown men were more concerned about paid work while women were more worried about childcare and shouldered more childcare work 51,52 . Furthermore, mothers experienced a greater decline in employment satisfaction while fathers' well-being was less affected and their family satisfaction even increased 53 . Another factor that could affect stress levels is domestic violence against women, which according to Israeli Police data, increased during lockdowns.…”
Section: Discussionmentioning
confidence: 98%
“…9131.04 (13) 8887.23 (28) 8964.54 (41) 9177.25 (23) 9640.40 (53) 9500. 24 (76) 9152.97 (37) 9407.81 (34) 9275.00 .…”
Section: Discussionmentioning
confidence: 99%
“…In another U.S. study [13], social distancing was associated with significantly higher levels of depression, anxiety, and insomnia, compared to levels measured before social distancing. Finally, in a German study [14], women reported a decrease in family and work satisfaction during lockdown compared to pre-lockdown levels.…”
Section: Introductionmentioning
confidence: 90%